Disiplin Siswa di Sekolah SMKN 1 Lubuk Basung - Dea Perdana Elsya; Irsyad Irsyad; Sufyarma Marsidin; Hanif Al Kadri (Journal of Educational Administration and Leadership, 2021)
This research is based on the author’s observation at SMKN 1 Lubuk Basung about student discipline that is still less than optimal. This study aims to obtain information about: 1) the elements of the discipline that are applied. 2) the teacher’s strategy of applying student discipline. 3) what stages the teacher does in instilling discipline. 4) efforts to perevent student behavior who are less disciplined. Descriptive quantitative is a type of research. With a population of students of SMKN 1 Lubuk Basung as many as 956 students. To find out the sample in this study is proportionate stratified random sampling, a sample of 109 students was obtained. This research instrument is a Likert Scale model questionnaire which has been tested for validity and reliability. The results showed that: 1) student discipline in the SMKN 1 Lubuk Basung school was still categorized as sufficient with an average score of 2,85. 2) student discipline regarding the application of discipline at SMKN 1 Lubuk Basung is still categorized as sufficient with an average score of 3,07. 3) student discipline about what stages